Characterization of a Mode of Specific Binding of Fibrin Monomer through its Amino-Terminal Domain by Macrophages and Macrophage Cell-Lines - Shainoff, John R; Stearns, Deborah J; DiBello, Patricia M; Hishikawa-Itoh, Youko (Thrombosis and Haemostasis, 1990)
The studies reported here probe the existence of a receptor-mediated mode of fibrin-binding by macrophages that is associated with the chemical change underlying the fibrinogen-fibrin conversion (the release of fibrinopeptides from the amino-terminal domain) without depending on fibrin-aggregation. The question is pursued by 1) characterization of binding in relation to fibrinopeptide content of both the intact protein and the CNBr-fragment comprising the amino-terminal domain known as the NDSK of the protein, 2) tests of competition for binding sites, and 3) photo-affinity labeling of macrophage surface proteins. The binding of intact monomers of types lacking either fibrinopeptide A alone (α-fibrin) or both fibrinopeptides A and B (αβ-fibrin) by peritoneal macrophages is characterized as proceeding through both a fibrin-specific low density/high affinity (BMAX ≃ 200–800 molecules/cell, KD ≃ 10−12 M) interaction that is not duplicated with fibrinogen, and a non-specific high density/low affinity (BMAX ≥ 105 molecules/cell, KD ≥ 10−6 M) interaction equivalent to the weak binding of fibrinogen. Similar binding characteristics are displayed by monocyte/macrophage cell lines (J774A.1 and U937) as well as peritoneal macrophages towards the NDSK preparations of these proteins, except for a slightly weaker (KD ≃ 10−10 M) high-affinity binding. The high affinity binding of intact monomer is inhibitable by fibrin-NDSK, but not fibrinogen-NDSK. This binding appears principally dependent on release of fibrinopeptide-A, because a species of fibrin (β-fibrin) lacking fibrinopeptide-B alone undergoes only weak binding similar to that of fibrinogen. Synthetic Gly-Pro-Arg and Gly-His-Arg-Pro corresponding to the N-termini of to the α- and the β-chains of fibrin both inhibit the high affinity binding of the fibrin-NDSKs, and the cell-adhesion peptide Arg-Gly-Asp does not. Photoaffinity-labeling experiments indicate that polypeptides with elec-trophoretically estimated masses of 124 and 187 kDa are the principal membrane components associated with specifically bound fibrin-NDSK. The binding could not be up-regulated with either phorbol myristyl acetate, interferon gamma or ADP, but was abolished by EDTA and by lipopolysaccharide. Because of the low BMAX, it is suggested that the high-affinity mode of binding characterized here would be too limited to function by itself in scavenging much fibrin, but may act cooperatively with other, less limited modes of fibrin binding.